FORMULASI DAN UJI EFEKTIVITAS SEDIAAN MASKER BUBUK ORGANIK DARI EKSTRAK DAUN KELENGKENG(DIMOCARPUS LONGAN) TERHADAP PERTUMBUHAN BAKTERI PROPIONIBACTERIUM ACNE - Anisa, Resti; Setiawan, Prayitno; Basir, Nasrawati (Jurnal Riset Kefarmasian Indonesia, 2025)
Longan leaves (Dimocarpus longan) contain flavonoids, phenols, tannins and saponins which are secondary metabolite compounds that have antibacterial activity. Antibacterials are substances that can interfere with the growth or even kill bacteria by interfering with the metabolism of harmful microbes. The aim of this research is to find out whether the organic powder mask preparation from longan leaf extract is stable and formulated physically and chemically, and to determine the results of the inhibitory power obtained from the organic powder mask preparation from longan leaf extract on the growth of Propionibacterium acne bacteria. This research method is experimental in vitro, with extraction using the Magnetic Stirrer Maceration method with 96% ethanol solvent, preliminary tests are carried out, then an Organic Powder mask formulation is made with concentrations of F1 (3%), F2 (4%), F3 (5% ). Then proceed with the antimicrobial effectiveness test against Propionibacterium acne bacteria The research results showed that there was no difference in the stability of the organic powder mask formulation (p>0.05) before and after the cycling test in organoleptic testing, pH testing, homogeneity, spreadability, dry time testing and particle size testing. Testing the Antibacterial Effectiveness of Propionibacterium acne showed that formula 1 (3%), formula 2 (4%) and formula 3 (5%) were effective against Propionibacterium acne bacteria with an average inhibition zone of 10.26 (medium), 11 respectively. .01 (strong) and 11.28 (strong). It can be concluded that longan leaf extract can be formulated as an organic powder mask preparation and has antibacterial effectiveness against Propionibacterium acne in the strong category at a concentration of 5% with an average diameter of the inhibition zone of 11.28